Dissection as the cause of thrombosis of internal carotid artery and the target for interventional treatment of the acute ischemic stroke - V. A. Saskin; I. A. Pankov; A. A. Zorin; M. V. Chasnyk; E. V. Nedashkovsky (Вестник анестезиологии и реаниматологии, 2019)
Acute ischemic stroke is a common cause of disability and mortality. In some rare cases, it can result from the structural changes in the major extracranial arteries, including vascular dissection. Due to the low incidence, the management of the acute period of dissection-associated stroke is not completely understood.In the clinical case presented, we describe the medical history of a forty years old patient in the acute period of cerebral infarction related to the dissection of the internal carotid artery, including the techniques and possible results of endovascular therapy. In this clinical scenario of acute stroke period, emergency angioplasty and stenting of carotid artery have been shown to be a highly effective approach.